Investigation of type 1 collagen a1 chain in plasma as a potential novel biomarker for prediction of coronary heart disease. (3rd October 2022) - Hammareus, F; Nilsson, L; Ong, K L; Kristenson, M; Festin, K; Lundberg, A; Chung, R W S; Swahn, E; Alfredsson, J; Holm Nielsen, S; Jonasson, L
Abstract: Background: Remodeling of the extracellular matrix (ECM) plays a crucial role in development and progression of atherosclerosis. Collagens, in particular type I collagen, are the most abundant ECM proteins in an atherosclerotic plaque. Recently, type I collagen α1 chain (COL1α1) in plasma was identified as a potential predictor of coronary heart disease (CHD). Aim: The aim was to further confirm the predictive value of COL1α1 and also to investigate its correlates in a population-based cohort as well as changes over time in patients with manifest CHD in Sweden. Methods: In a total of 1007 well-characterized individuals (50% women), 86 CHD cases and 184 sex- and age-matched controls were identified at 13 years follow-up. CHD at follow-up was defined as first-time event of myocardial infarction (MI) or invasive coronary intervention. Plasma levels of COL1α1 was quantified by the Luminex assay while PRO-C1 and C1M, two markers of type I collagen synthesis and degradation, respectively, were quantified by ELISA. In Cox proportional hazard analysis, log2 values of biomarker levels were used. In addition, temporal change of COL1α1 levels was also examined in a cohort of 125 patients with acute MI followed for 6 months. Results: COL1α1 levels were significantly associated with incident CHD, both unadjusted (HR = 0.69, 95% CI 0.56–0.87, p=0.001) and after multiple adjustment (HR = 0.55, 95% CI 0.41–0.75, p<0.001). PRO-C1 was similarly associated with CHD, unadjusted (HR = 0.62, 95% CI 0.47–0.82, p=0.001) as well as adjusted (HR = 0.61, 95% CI 0.43–0.86, p=0.005), while C1M was not. In patients with acute MI, COL1α1 levels remained stable over 6 months. COL1α1 was significantly correlated to PRO-C1 (r=0.73, p<0.001), while there were no correlations to C1M, markers of inflammation (C-reactive protein, interleukin-6, matrix metalloproteinase-9) or myocardial injury (troponin T). Conclusions: Circulating COL1α1 in plasma was independently and inversely associated with incident CHD. Furthermore, COL1α1 levels appeared to be relatively stable after an acute MI. COL1α1 levels seem to reflect collagen synthesis rather than collagen degradation and inflammation. Future studies are needed to confirm whether COL1α1 is a clinically useful marker and/or predictor of CHD. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): This research was in part financed by a grant from the Region of Östergötland, Sweden, aimed towards scientists early in their career. We would like to thank the people behind this grant for contributing to this research.This research was also partly supported by Futurum - the academy for healthcare in Region Jönköping County.